2022
DOI: 10.5267/j.msl.2021.8.001
|View full text |Cite
|
Sign up to set email alerts
|

Does workplace spirituality influence knowledge-sharing behavior and work engagement in work? Trust as a mediator

Abstract: Management scholars view workplace spirituality as the main factor behind building trust among employees and playing a pivotal role in enhancing the organization's positive outcomes, i.e., knowledge sharing behavior & work engagement. Underpinning social exchange theory, we explored the linkage between workplace spirituality, knowledge sharing behavior, and work engagement. We further studied to look at the mediating effect of trust between workplace spirituality and positive outcomes. Data was collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 87 publications
(137 reference statements)
2
28
0
Order By: Relevance
“…The knowledge management literature has demonstrated the importance of leadership in establishing rules and directions that encourage KS ( Lin et al, 2020 ). Several studies have indicated that ethical leaders motivate their followers to participate in pro-social activities, such as sharing knowledge and assisting others to gain knowledge ( Gerpott et al, 2020 ; He et al, 2021 ), while reducing deviance ( Evans et al, 2021 ; Khan et al, 2022 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The knowledge management literature has demonstrated the importance of leadership in establishing rules and directions that encourage KS ( Lin et al, 2020 ). Several studies have indicated that ethical leaders motivate their followers to participate in pro-social activities, such as sharing knowledge and assisting others to gain knowledge ( Gerpott et al, 2020 ; He et al, 2021 ), while reducing deviance ( Evans et al, 2021 ; Khan et al, 2022 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“… 39 It is conceived as a multidimensional approach seeking meaning and purpose in life. 40–42 Pioneering research on workplace spirituality, which included the transcendental component, found seven different elements of WPS. 25 Petchsawang and Duchon 43 workplace spirituality is defined as having feelings of grateful to others, having inner satisfaction to perform job roles and having passion towards organizational values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the power-sharing behavior of leaders is significantly related to the motivation and performance of employees for the accomplishment of collective goals that eventually enhance workplace performance ( Chua et al, 2012 ; Khan et al, 2022 ). Employees who feel that their work and efforts are being admired are motivated to perform better ( Liden et al, 2000 ; Ali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%